Structural Inequalities in Educational Leadership: Addressing Social and Professional Identities and Recognitional Power - Duygun Göktürk; Özge Çomak (Journal of Economy Culture and Society)
In this article, we aim to work toward a rich theoretical understanding of the relationship between social identity, professional identity, and school leadership in the context of recognitional power. We approach the relationship the study constructs by problematizing the traditional areas of leadership literature that is marked by veneration of leadership and its functional toolkit that includes traits, attitudes, behaviors, efficiency, productivity, mastery, etc. as antecedents to the leadership process. In addition, the article aims to capture the intersection of professional and social identity considering the relations of domination and everyday practices of recognition. These goals are reflected in two research questions: (1) How do we understand the relationship between school leadership, social identity and professional identity? (2) How do we approach social and professional identities in educational leadership studies in terms of recognitional power? We propound that leadership literature should include diverse epistemic approaches, problematize the structural inequalities and the institutionalized relations of recognition and recognitional power, and problematize the intersection of social identity, professional identity, and recognitional power.